Comparison of a Nasal Mask and Traditional Nasal Cannula During Intravenous Anesthesia for Gastroscopy Procedures: A Randomized Controlled Trial. (March 2022) - Chen, Dong Xu; Yang, Hui; Wu, Xi Ping; Niu, Wang; Ding, Lin; Zeng, Huo Lin; Li, Qian
Abstract : BACKGROUND: Hypoxemia can occur during gastroscopy under intravenous anesthesia. The aim of this randomized controlled trial was to evaluate whether oxygenation using a nasal mask can reduce the incidence of hypoxemia during gastroscopy under intravenous anesthesia compared with a traditional nasal cannula. METHODS: A total of 574 patients scheduled for gastroscopy under intravenous anesthesia were enrolled and randomly assigned to receive either a nasal mask or a traditional nasal cannula for oxygenation. The primary outcome was the incidence of hypoxemia. The secondary outcomes included the incidence of severe hypoxemia, duration of hypoxemia, minimum oxygen saturation, the proportion of emergency airway management, length of procedure, recovery time, and the satisfaction of the anesthetist and gastroenterologists as well as other adverse events (including cough, hiccups, nausea and vomiting, reflux, aspiration, and laryngospasm). RESULTS: A total of 565 patients were included in the analysis: 282 patients in the nasal cannula group and 283 patients in the nasal mask group. The incidence of hypoxemia was lower in the nasal mask group (18.0%) than in the nasal cannula group (27.7%; relative risk [RR] = 0.65; 95% confidence interval [CI], 0.48–0.89; P = .006), and the hypoxemia lasted a median of 18.0 seconds (interquartile range, 10.0–38.8) in the nasal mask group and 32.5 seconds (20.0–53.5) in the nasal cannula group (median difference –14.50; 95% CI, −22.82 to −1.34; P = .047). The proportion of patients requiring emergency airway management was significantly lower in the nasal mask group (8.8%) than in the nasal cannula group (19.1%; RR, 0.46; 95% CI, 0.30–0.73; P < .001). No difference was found in the overall incidence of other adverse events between the 2 groups (nasal mask 20.8%; nasal cannula 17.0%; RR, 1.23; 95% CI, 0.87–1.73; P = .25). Satisfaction was higher with the nasal mask than with the nasal cannula from the perspective of anesthetists (96.1% for nasal mask versus 84.4% for nasal cannula; RR, 1.14; 95% CI, 1.08–1.20; P < .001) and gastroenterologists (95.4% for mask versus 81.9% for cannula; RR, 1.17; 95% CI, 1.10–1.24; P < .001). There were no significant differences in the incidence of severe hypoxemia, minimum oxygen saturation, length of procedure, or recovery time between the 2 groups. CONCLUSIONS: Nasal mask oxygenation reduced the incidence of hypoxemia during anesthesia for gastroscopy under intravenous anesthesia.